Cerium oxide composite abrasive particle with core-shell structure as well as preparation method and application of cerium oxide composite abrasive particle

By adopting core-shell structured ceria composite abrasive particles, combined with hydrothermal method and in-situ chemical precipitation method, the existing ceria abrasives have been solved, and the problem of poor wear resistance and low material removal rate during polishing is achieved. More efficient and stable polishing effect.

CN119490818AActive Publication Date: 2025-02-21FUDAN UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411649415.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-21
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing ceria abrasives have problems such as poor wear resistance, high wafer surface roughness and low material removal rate during chemical mechanical polishing.

Method used

The ceria composite abrasive particles with a core-shell structure, including a core composed of solid ceria nanospheres and a clad shell layer composed of mesoporous ceria nanomaterials, were prepared by hydrothermal method and in-situ chemical precipitation method.

Benefits of technology

It improves the wear resistance and chemical reactivity of abrasive particles, significantly improves the material removal rate and polishing efficiency, and reduces the roughness of the wafer surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490818A_ABST
    Figure CN119490818A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polishing materials, and relates to a cerium oxide composite abrasive particle with a core-shell structure as well as a preparation method and application of the cerium oxide composite abrasive particle. The cerium oxide composite abrasive particle with the core-shell structure comprises an inner core formed by solid cerium oxide nanospheres and a coating shell layer formed by mesoporous cerium oxide nanomaterials. The inner core structure of the cerium oxide composite abrasive particle is compact, and the coating shell layer has a rich pore structure and a large specific surface area. The surface layer of the cerium oxide composite abrasive particles is mesoporous cerium oxide, so that the roughness of the surface of the wafer can be reduced. The internal support provided by the inner core can reduce the collapse of the mesoporous cerium oxide nano material, so that the cerium oxide composite abrasive particle has better wear resistance. Compared with a single cerium oxide particle, the cerium oxide composite abrasive particle disclosed by the invention has the advantages that the chemical reaction activity and the material removal rate are remarkably improved, and the material removal rate, the polishing efficiency and the surface quality can be remarkably improved in the ultra-precision surface polishing process, so that the requirements of a high-precision manufacturing process in the modern chip industry are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polishing materials, and in particular to a cerium oxide composite abrasive grain with a core-shell structure, a preparation method and application thereof. Background Art

[0002] Since the invention of the integrated circuit (IC), the semiconductor industry has undergone several technological revolutions, continuously pushing electronic products towards miniaturization, high performance and low power consumption. During the chip manufacturing process, the requirements for planarization technology are also increasing. The quality of the planarization process directly affects the performance and yield of the chip.

[0003] Chemical mechanical polishing (CMP) is a planarization technology widely used in integrated circuit manufacturing. It combines chemical etching with mechanical grinding to planarize the material surface by using the abrasive particles and chemical reagents in the abrasive suspension.

[0004] Abrasive particles (abrasive grains) are the core component of the chemical mechanical polishing process, and their performance directly affects the polishing effect and surface quality. According to their materials and characteristics, polishing abrasives can be divided into many types, including aluminum oxide abrasives, silicon oxide abrasives and cerium oxide abrasives. Among them, cerium oxide abrasives are widely favored due to their high chemical reactivity and excellent mechanical properties. At present, there are also many studies on cerium oxide abrasives with different morphologies, such as solid cerium oxide nanospheres, mesoporous cerium oxide nanospheres and cerium oxide nanoclusters. Among them, solid cerium oxide nanosphere particles have good wear resistance and stability due to their dense internal structure, but their specific surface area is low, which limits their chemical reactivity, resulting in a low material removal rate during chemical mechanical polishing, and the solid cerium oxide nanosphere particles will cause the surface roughness of the wafer to be higher after polishing the wafer. Mesoporous cerium oxide particles have a rich pore structure and a large specific surface area, providing more chemical reaction sites and significantly improving the chemical reaction activity and material removal rate. However, the porous structure makes their hardness insufficient, resulting in poor wear resistance and easy structural collapse. During long-term or high-intensity polishing, accelerated wear may occur.

[0005] Therefore, it is necessary to provide an abrasive that has high wear resistance, good polishing effect and high material removal rate, so as to make up for the defects of a single abrasive and provide a more efficient and stable polishing solution. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In order to solve the problems in the prior art of poor wear resistance of single cerium oxide abrasives, high roughness of the wafer surface and low material removal rate, the present invention provides a cerium oxide composite abrasive with a core-shell structure, a preparation method and application thereof.

[0008] (II) Technical solution

[0009] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0010] In a first aspect, the present invention provides a cerium oxide composite abrasive grain having a core-shell structure, comprising an inner core composed of solid cerium oxide nanospheres and a coating shell composed of a mesoporous cerium oxide nanomaterial.

[0011] As for the cerium oxide composite abrasive grains with a core-shell structure as described above, preferably, the core is made of solid cerium oxide nanospheres subjected to surface modification treatment with polyethyleneimine.

[0012] As for the cerium oxide composite abrasive grains with a core-shell structure as described above, preferably, the diameter of the core is 100-200 nm, and the thickness of the coating shell is 10-50 nm.

[0013] As for the cerium oxide composite abrasive grains with a core-shell structure as described above, preferably, the diameter of the core is 100-160 nm, and the thickness of the coating shell is 10-25 nm.

[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned cerium oxide composite abrasive having a core-shell structure, comprising the following steps:

[0015] S1: Preparation of solid cerium oxide nanospheres by hydrothermal method;

[0016] S2: Surface modification of solid cerium oxide nanospheres by polyethyleneimine;

[0017] S3: The mesoporous cerium oxide nanomaterial is coated on the surface of the solid cerium oxide nanospheres after surface modification by an in-situ chemical precipitation method to obtain cerium oxide composite abrasives.

[0018] In the method for preparing the cerium oxide composite abrasive grains having a core-shell structure as described above, preferably, step S1 comprises the following steps:

[0019] S11: subjecting a cerium source, a structure directing agent, and a precipitating agent to a hydrothermal reaction to obtain a cerium oxide precursor;

[0020] S12: calcining the cerium oxide precursor to obtain solid cerium oxide nanospheres;

[0021] In step S11, the cerium source is cerium nitrate hexahydrate, the structure directing agent is polyethylene glycol, and the precipitant is urea; the molar ratio of urea to cerium nitrate hexahydrate is 25-150, and the molecular weight of polyethylene glycol is 4000-20000Da; the temperature of the hydrothermal reaction is 90-110°C, and the time of the hydrothermal reaction is 2.5-3.5h;

[0022] In step S12, calcination is performed in an air atmosphere at a temperature of 500-600° C. and a calcination time of 2-4 hours.

[0023] In the method for preparing the cerium oxide composite abrasive grains having a core-shell structure as described above, preferably, step S2 comprises the following steps:

[0024] The solid cerium oxide nanospheres are dispersed in water, polyethyleneimine is added, ultrasonically reacted for 20-30 minutes, and then post-treated to obtain solid cerium oxide nanospheres with surface modification.

[0025] The molecular weight of polyethyleneimine is 10000-15000 Da.

[0026] In the method for preparing the cerium oxide composite abrasive grains having a core-shell structure as described above, preferably, step S3 comprises the following steps:

[0027] S31: adding the surface-modified solid cerium oxide nanospheres, citric acid, hexadecyltrimethylammonium bromide, sodium salicylate, hexamethylenetetramine, cerium chloride hexahydrate and cyclohexane into deionized water, stirring the mixture, and then reacting the mixture under heating and stirring conditions to obtain solid cerium oxide nanospheres with mesoporous cerium hydroxide nanomaterials coated on the surface;

[0028] S32: calcining the solid cerium oxide nanospheres whose surfaces are coated with mesoporous cerium hydroxide nanomaterials to obtain cerium oxide composite abrasive particles.

[0029] The method for preparing the cerium oxide composite abrasive grains having a core-shell structure as described above, preferably,

[0030] In step S31, the mass ratio of sodium salicylate to solid cerium oxide nanospheres is 4:1-6:1. After each component is added to deionized water, the concentration of citric acid is 0.05-0.15 g / L, the concentration of hexadecyltrimethylammonium bromide is 1-3 g / L, the concentration of sodium salicylate is 1-2 g / L, the concentration of hexamethylenetetramine is 0.2-0.4 g / L, the concentration of cerium chloride hexahydrate is 1.5-2 g / L, and the volume ratio of cyclohexane to deionized water is (2-4):(9-11); the stirring time is 1-2 h, the heating temperature is 60-80 ° C, and the reaction time is 7-8 h;

[0031] In step S32, the solid cerium oxide nanospheres with the surface coated with the mesoporous cerium hydroxide nanomaterial are first subjected to a first-stage calcination treatment under a protective atmosphere, and then the solid cerium oxide nanospheres with the surface coated with the mesoporous cerium hydroxide nanomaterial are subjected to a second-stage calcination treatment under an air atmosphere;

[0032] The calcination temperature of the first stage calcination treatment is 500-600℃, and the calcination time is 4-6h;

[0033] The calcination temperature of the second stage calcination treatment is 500-600°C and the calcination time is 2-4h.

[0034] In a third aspect, the present invention further provides an application of the cerium oxide composite abrasive grains or the cerium oxide composite abrasive grains prepared by the above-mentioned preparation method, wherein the cerium oxide composite abrasive grains are used in a polishing liquid.

[0035] (III) Beneficial effects

[0036] The present invention provides a new cerium oxide composite abrasive grain with a core-shell structure, comprising a core composed of solid cerium oxide nanospheres and a coating shell composed of mesoporous cerium oxide nanomaterials. The core-shell structured cerium oxide composite abrasive grain has a stable structure, integrates the advantages of solid cerium oxide nanospheres and mesoporous cerium oxide nanomaterials, has a dense core structure, and has a rich pore structure and a large specific surface area.

[0037] The surface layer of the cerium oxide composite abrasive of the present invention is mesoporous cerium oxide, and after polishing the wafer, the roughness of the wafer surface can be reduced. In the cerium oxide composite abrasive of the present invention, the solid cerium oxide nanospheres in the inner core provide a solid internal support, which can reduce the deformation and collapse of the mesoporous cerium oxide nanomaterial, enhance the overall strength and wear resistance of the coating shell layer, and make the cerium oxide composite abrasive have better wear resistance and reduce wear. In addition, compared with single solid cerium oxide nanospheres and mesoporous cerium oxide nanomaterials, the chemical reaction activity and material removal rate of the cerium oxide composite abrasive with a core-shell structure are significantly improved.

[0038] Therefore, the cerium oxide composite abrasive with a core-shell structure in the present invention can significantly improve the material removal rate, polishing efficiency and surface quality during the polishing of ultra-precision surfaces to meet the requirements of high-precision manufacturing processes in the modern chip industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 a- Figure 1 f are transmission electron microscopy images of solid cerium oxide nanospheres prepared in Examples 1-6;

[0040] Figure 2 a is a transmission electron microscopy image of sCeO2-mCeO2 prepared in Example 7;

[0041] Figure 2 b is Figure 2 A partial enlarged view of a;

[0042] Figure 3 This is a transmission electron microscope image of the product prepared in Comparative Example 1;

[0043] Figure 4 XRD curves of sCeO2 prepared in Example 2 and sCeO2-mCeO2 prepared in Example 7;

[0044] Figure 5 This is the N2 adsorption-desorption isotherm diagram of sCeO2-mCeO2 prepared in Example 7;

[0045] Figure 6 This is the pore size distribution diagram of sCeO2-mCeO2 prepared in Example 7;

[0046] Figure 7a This is the XPS curve of sCeO2 prepared in Example 2;

[0047] Figure 7b XPS curve of sCeO2-mCeO2 prepared in Example 7;

[0048] Figure 8a Two-dimensional AFM topography of the surface of the silicon oxide wafer after polishing the silicon oxide wafer using the polishing solution prepared with sCeO2-mCeO2 prepared in Example 7;

[0049] Figure 8b This is a three-dimensional AFM morphology image of the surface of a silicon oxide wafer after the silicon oxide wafer is polished using the polishing solution prepared with sCeO2-mCeO2 prepared in Example 7. DETAILED DESCRIPTION

[0050] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods.

[0051] The invention provides a cerium oxide composite abrasive grain with a core-shell structure, comprising a core composed of solid cerium oxide nanospheres and a coating shell composed of mesoporous cerium oxide nanomaterials.

[0052] The cerium oxide composite abrasive with a core-shell structure in the present invention integrates the advantages of solid cerium oxide nanospheres and mesoporous cerium oxide nanomaterials, with a dense core structure and a coating shell layer having a rich pore structure and a high specific surface area. The strength of the cerium oxide composite abrasive is improved, and the overall strength is between that of solid cerium oxide nanospheres and mesoporous cerium oxide nanomaterials. The surface layer is mesoporous cerium oxide, and the polishing effect is close to that of mesoporous cerium oxide nanomaterials. Compared with single cerium oxide nanosphere abrasives, the roughness of the wafer surface can be reduced.

[0053] In the cerium oxide composite abrasive of the present invention, the solid cerium oxide nanospheres in the inner core provide solid internal support, which can effectively disperse and absorb stress, reduce the deformation and collapse of the mesoporous cerium oxide nanomaterials, and enhance the overall strength and wear resistance of the coating shell layer, so that the cerium oxide composite abrasive has better wear resistance and reduces the wear of the abrasive during long-term or high-intensity polishing.

[0054] In addition, compared with a single solid cerium oxide nanosphere and a single mesoporous cerium oxide nanomaterial, the content of trivalent cerium ions in the cerium oxide composite abrasive with a core-shell structure is increased, and the chemical reaction activity and the material removal rate are significantly improved. The material removal rate is increased by about 40-50% compared with a single solid cerium oxide nanosphere (under the same abrasive concentration in the polishing liquid), and the content of trivalent cerium ions can be increased by up to 20-30%. Compared with a single mesoporous cerium oxide nanomaterial, the material removal rate is increased by about 20-30% (under the same abrasive concentration in the polishing liquid).

[0055] Therefore, the cerium oxide composite abrasive with a core-shell structure in the present invention can significantly improve the material removal rate, polishing efficiency and surface quality during the polishing of ultra-precision surfaces to meet the requirements of high-precision manufacturing processes in the modern chip industry.

[0056] Preferably, the inner core of the cerium oxide composite abrasive is made of solid cerium oxide nanospheres subjected to surface modification treatment with polyethyleneimine. The diameter of the inner core is preferably 100-200 nm, more preferably 100-160 nm, more preferably 120 nm, 130 nm, 135 nm, 140 nm and 150 nm, etc., and the thickness of the coating shell is preferably 10-50 nm, more preferably 10-25 nm, more preferably 10 nm, 20 nm, 25 nm, 30 nm, 40 nm and 50 nm.

[0057] Surface modification by polyethyleneimine is the key to successfully coating the coating shell on the surface of solid cerium oxide nanospheres to form a core-shell structure. If the solid cerium oxide nanospheres in the present invention are not surface modified by polyethyleneimine, the mesoporous cerium hydroxide / cerium oxide nanomaterial cannot be coated on the surface of the solid cerium oxide nanospheres, and the cerium oxide composite abrasive with a core-shell structure cannot be obtained.

[0058] In the present invention, the diameter and thickness range of the core and the coating shell directly determine the polishing effect of the cerium oxide composite abrasive. If the diameter of the core is less than 100nm and the thickness of the coating shell is less than 10nm, the particle size of the cerium oxide composite abrasive grains will be too small, which will reduce the material removal rate and polishing efficiency. Moreover, the cerium oxide composite abrasive grains with too small particle size have a high affinity with the wafer and are easy to adhere to the wafer surface after polishing and are difficult to clean and remove. If the diameter of the core is greater than 200nm and the thickness of the coating shell is greater than 40nm, the particle size of the cerium oxide composite abrasive grains will be too large, increasing the scratches on the wafer surface, and the scratches are wider, resulting in a higher roughness on the wafer surface after polishing, which affects the subsequent process of the chip.

[0059] The present invention also provides a method for preparing the above-mentioned cerium oxide composite abrasive grains having a core-shell structure, comprising the following steps:

[0060] S1: Preparation of solid cerium oxide nanospheres by hydrothermal method.

[0061] S2: Surface modification of solid cerium oxide nanospheres by polyethyleneimine.

[0062] S3: The mesoporous cerium oxide nanomaterial is coated on the surface of the solid cerium oxide nanospheres after surface modification by an in-situ chemical precipitation method to obtain cerium oxide composite abrasives.

[0063] The hydrothermal method and the chemical precipitation method are both common methods for synthesizing nanomaterials. The hydrothermal method refers to a method of preparing a powder by placing a certain form of precursor in an autoclave aqueous solution, performing a hydrothermal reaction under high temperature and high pressure conditions, and then performing post-treatments such as separation, washing, and drying. The chemical precipitation method refers to a method of preparing a nanomaterial by heat-treating the precipitate after adding a precipitant to a salt solution for reaction. Theoretically, there are no special restrictions on the raw materials, equipment, and steps used for the hydrothermal method and the chemical precipitation method. However, the present invention obtains a core-shell structure nanomaterial with relatively better performance and better physical and chemical morphology through the special selection of raw materials and the regulation of experimental conditions.

[0064] Preferably, the above step S1 specifically includes the following steps:

[0065] S11: subjecting a cerium source, a structure directing agent and a precipitating agent to a hydrothermal reaction to obtain a cerium oxide precursor.

[0066] S12: calcining the cerium oxide precursor to obtain solid cerium oxide nanospheres.

[0067] Wherein, in step S11, the cerium source is preferably cerium nitrate hexahydrate, the structure directing agent is preferably polyethylene glycol, the precipitating agent is preferably urea, the molar ratio of urea to cerium nitrate hexahydrate is 25-150, the molecular weight of polyethylene glycol is 4000-20000Da, the temperature of the hydrothermal reaction is 90-110°C, preferably 100°C, and the time of the hydrothermal reaction is 2.5-3.5h, preferably 3h.

[0068] In step S12, calcination is performed in an air atmosphere at a temperature of 500-600° C. and a calcination time of 2-4 hours.

[0069] Furthermore, in the above step S11, urea and deionized water may be mixed to prepare solution A, cerium nitrate hexahydrate, polyethylene glycol and deionized water may be mixed to prepare solution B, and then solution A and solution B may be evenly mixed, transferred to a hydrothermal reactor, and placed in a forced air drying oven for heating reaction. The concentration of urea in solution A is preferably 2-6 mol / L, the concentration of cerium nitrate hexahydrate in solution B is preferably 0.01-0.04 mol / L, and the amount of polyethylene glycol in solution B is 0.04-0.06 g per milliliter of deionized water.

[0070] After the hydrothermal reaction is completed, the solid particles of cerium oxide precursor are obtained after cooling, separation, washing and drying, wherein the drying temperature is 60-70° C. and the drying time is 8-12 hours.

[0071] In the above hydrothermal reaction, solid cerium oxide nanosphere materials with different particle size distributions can be prepared by adjusting the amount or type of raw materials, such as the amount of cerium nitrate hexahydrate and urea, and the molecular weight of PEG.

[0072] Preferably, the above step S2 includes the following steps:

[0073] Solid cerium oxide nanospheres are dispersed in water, polyethyleneimine is added, ultrasonic reaction is performed for 20-30 minutes, and then post-treatment is performed to obtain solid cerium oxide nanospheres with surface modification.

[0074] The molecular weight of polyethyleneimine is preferably 10000-15000 Da, more preferably 10000 Da.

[0075] Furthermore, in step S2, the solid cerium oxide nanospheres prepared in step S1 can be dispersed in deionized water, and then mixed with polyethyleneimine to prepare solution C, and ultrasonic reaction is performed on solution C. After the ultrasonic reaction, solution C is separated and washed, and the washed solid is redispersed in deionized water to obtain a standby solution D.

[0076] Further preferably, the concentration of solid cerium oxide nanospheres in solution C is 0.1-0.2 g / L, more preferably 0.15 g / L, the concentration of polyethyleneimine is 0.2-0.3 g / L, more preferably 0.25 g / L, and the mass ratio of polyethyleneimine to solid cerium oxide nanospheres is preferably 5:3.

[0077] Preferably, the above step S3 includes the following steps:

[0078] S31: Add surface-modified solid cerium oxide nanospheres, citric acid, hexadecyltrimethylammonium bromide, sodium salicylate, hexamethylenetetramine, cerium chloride hexahydrate and cyclohexane into deionized water, stir, and then react the mixed system under heating and stirring conditions to obtain solid cerium oxide nanospheres with surface-coated mesoporous cerium hydroxide nanomaterials. Among them, cyclohexane is the oil phase, deionized water is the water phase, cerium chloride hexahydrate is the cerium source, hexadecyltrimethylammonium bromide is the structure directing agent, hexamethylenetetramine is the precipitant, citric acid is the chelating agent, and sodium salicylate is the viscosity regulator. The water-oil two phases help to form dendritic mesoporous materials. Sodium salicylate helps to form spherical mesoporous nanomaterials on the one hand, and can provide appropriate viscosity on the other hand, which is conducive to the adhesion of cerium hydroxide to the surface of solid cerium oxide nanospheres, thereby forming a tight core-shell structure.

[0079] S32: calcining the solid cerium oxide nanospheres coated with the mesoporous cerium hydroxide nanomaterial to obtain cerium oxide composite abrasive grains. The mesoporous cerium hydroxide nanomaterial is prepared in step S31, and the mesoporous cerium oxide nanomaterial is obtained by the calcination treatment in step S32.

[0080] In step S31, citric acid, hexadecyltrimethylammonium bromide, sodium salicylate, hexamethylenetetramine, cerium chloride hexahydrate and cyclohexane can be mixed with the above-mentioned solution D containing solid cerium oxide nanospheres that have been surface modified, and then stirred vigorously to obtain solution E, and then continue to react under heating and stirring conditions.

[0081] The mass ratio of sodium salicylate to solid cerium oxide nanospheres is 4:1-6:1, preferably 5:1. In solution E, the concentration of citric acid is 0.05-0.15 g / L, the concentration of hexadecyltrimethylammonium bromide is 1-3 g / L, the concentration of sodium salicylate is 1-2 g / L, the concentration of hexamethylenetetramine is 0.2-0.4 g / L, the concentration of cerium chloride hexahydrate is 1.5-2 g / L, and the volume ratio of cyclohexane to deionized water is (2-4):(9-11); the stirring time is 1-2 h, the heating temperature is 60-80° C., preferably 70° C., and the reaction time is 7-8 h. Furthermore, in solution E, the concentration of citric acid is preferably 0.1 g / L, the concentration of hexadecyltrimethylammonium bromide is preferably 2 g / L, the concentration of sodium salicylate is preferably 1.5 g / L, the concentration of hexamethylenetetramine is preferably 0.3 g / L, the concentration of cerium chloride hexahydrate is preferably 1.5-2 g / L, and the volume ratio of cyclohexane to deionized water is preferably 3:10.

[0082] In step S31, after the heating reaction of solution E is completed, it is cooled, separated, washed, and dried to obtain solid cerium oxide nanospheres with surface coated with mesoporous cerium hydroxide nanomaterials. The drying temperature is preferably 60-70°C, and the drying time is preferably 8-12h.

[0083] In step S32, the calcination is divided into two stages. First, the solid cerium oxide nanospheres with the surface coated with the mesoporous cerium hydroxide nanomaterial are subjected to a first-stage calcination treatment under a protective atmosphere, and then the solid cerium oxide nanospheres with the surface coated with the mesoporous cerium hydroxide nanomaterial are subjected to a second-stage calcination treatment under an air atmosphere. Further preferably, the calcination temperature of the first-stage calcination treatment is 500-600° C., the calcination time is 4-6 hours, the protective gas of the first stage can be nitrogen, and the calcination temperature of the second-stage calcination treatment is 500-600° C., and the calcination time is 2-4 hours.

[0084] The polyethyleneimine in the present invention is positively charged, and the surface modification treatment of the solid cerium oxide nanosphere material is performed by using the polyethyleneimine, which can make the surface of the solid cerium oxide nanosphere material carry a positive charge on the one hand, and is conducive to improving the dispersibility of the solid cerium oxide nanosphere on the other hand, so that in the subsequent synthesis of the mesoporous cerium hydroxide nanomaterial, the citric acid chelating agent, one of the raw materials, carries a negative charge, so that the solid cerium oxide nanosphere with a positive surface charge can attract the negatively charged citric acid, which is conducive to the in-situ precipitation of the mesoporous cerium hydroxide shell on the surface of the solid cerium oxide nanosphere, and obtains the cerium oxide composite abrasive with uniform particle size, and its uniform particle size can ensure the stability and consistency during the polishing process. If the surface modification treatment of polyethyleneimine is not performed in step S2, the mesoporous cerium hydroxide nanomaterial cannot be coated on the surface of the solid cerium oxide nanosphere.

[0085] The present invention also provides an application of the cerium oxide composite abrasive grains or the cerium oxide composite abrasive grains prepared by the above-mentioned preparation method. Specifically, the cerium oxide composite abrasive grains can be used in a polishing liquid.

[0086] Preferably, the cerium oxide composite abrasive can be added to deionized water to obtain a polishing slurry with a mass concentration of 0.2-0.5wt%, and the pH value of the polishing slurry is adjusted to about 4 with an acidic reagent such as acetic acid to obtain a polishing liquid, which is used in chip preparation.

[0087] In addition, the hardness of the cerium oxide composite abrasive of the present invention is between that of solid cerium oxide nanospheres and mesoporous cerium oxide nanomaterials. It has appropriate hardness, can effectively remove materials, and is not easy to cause scratches and damage to the chip surface. It also has good chemical stability, stable chemical properties in the polishing liquid, not easy to chemically react or decompose, can ensure the controllability of the polishing process, and has high purity, which can avoid the influence of impurities on the polishing effect and the surface quality of the chip.

[0088] Therefore, the cerium oxide composite abrasive particles of the present invention can effectively integrate the above-mentioned advantageous properties and improve the overall performance of the polishing liquid.

[0089] In order to further clarify the scheme of the present invention and its technical advancement, the following is a description in conjunction with specific embodiments and technical effects.

[0090] Example 1

[0091] This embodiment provides a method for preparing solid cerium oxide nanospheres, comprising the following steps:

[0092] Urea was dissolved in deionized water to obtain solution A, and stirred at room temperature for 30 min. Ce nitrate hexahydrate and polyethylene glycol (PEG) were dissolved in deionized water to obtain solution B, and stirred at room temperature for 30 min. Solution A and solution B were mixed and stirred for 1 hour.

[0093] The mixed solution was then transferred into a hydrothermal reactor and reacted at 100° C. for 3 h. After the reaction was completed, the solid was cooled and centrifuged to obtain a solid, which was washed with ethanol and deionized water respectively, and then dried in a drying oven at 60° C. overnight to obtain a cerium oxide precursor.

[0094] Finally, the dried cerium oxide precursor was calcined in a muffle furnace at 500° C. for 2 h to obtain a solid cerium oxide nanosphere material.

[0095] In this embodiment, the molecular weight of PEG is 4000Da, the molar ratio of urea to cerium nitrate hexahydrate is 25, the concentration of urea in solution A is 2 mol / L, the concentration of cerium nitrate hexahydrate in solution B is 0.0267 mol / L, and the amount of PEG in solution B is 1.6 g per 30 mL of deionized water.

[0096] Example 2-Example 6

[0097] Embodiment 2-embodiment 6 provide a method for preparing solid cerium oxide nanospheres, which differs from embodiment 1 in that:

[0098] In Example 2, the molecular weight of PEG is 20000 Da, the molar ratio of urea to cerium nitrate hexahydrate is 40:0.6, the concentration of urea in solution A is 4 mol / L, and the concentration of cerium nitrate hexahydrate in solution B is 0.02 mol / L.

[0099] In Example 3, the molecular weight of PEG is 20000 Da, the molar ratio of urea to cerium nitrate hexahydrate is 100, the concentration of urea in solution A is 4 mol / L, and the concentration of cerium nitrate hexahydrate in solution B is 0.0133 mol / L.

[0100] In Example 4, the molecular weight of PEG is 20000 Da, the molar ratio of urea to cerium nitrate hexahydrate is 50, the concentration of urea in solution A is 6 mol / L, and the concentration of cerium nitrate hexahydrate in solution B is 0.04 mol / L.

[0101] In Example 5, the molecular weight of PEG is 20000 Da, the molar ratio of urea to cerium nitrate hexahydrate is 60, the concentration of urea in solution A is 6 mol / L, and the concentration of cerium nitrate hexahydrate in solution B is 0.0333 mol / L.

[0102] In Example 6, the molecular weight of PEG is 20000 Da, the molar ratio of urea to cerium nitrate hexahydrate is 150, the concentration of urea in solution A is 6 mol / L, and the concentration of cerium nitrate hexahydrate in solution B is 0.0133 mol / L.

[0103] Figure 1 a- Figure 1 f shows the transmission electron microscope (TEM) images of the solid cerium oxide nanospheres prepared in Examples 1-6. Figure 1It can be seen that the solid cerium oxide nanospheres of Examples 1-6 all present a relatively uniform spherical structure, and the particle size (sphere diameter) is about 120-160nm. Specifically, the average particle sizes of the solid cerium oxide nanospheres prepared in Examples 1-6 are 135nm, 130nm, 140nm, 160nm, 160nm and 150nm, respectively. It can be seen that by properly adjusting the amount of the raw materials used or the molecular weight of PEG, solid cerium oxide nanosphere materials (sCeO2) with excellent morphology and adjustable size can be obtained.

[0104] Example 7

[0105] In this example, the sCeO2 prepared in Example 2 is treated as follows:

[0106] First, sCeO2 was surface-modified with polyethyleneimine (PEI) as follows: sCeO2 was dissolved in deionized water, and then the mixture was added to deionized water containing PEI to obtain solution C. Solution C was ultrasonically dispersed for 20 min, centrifuged, and washed with deionized water, and then the sCeO2 with the surface modified by PEI was redispersed in deionized water to obtain solution D.

[0107] Secondly, mesoporous cerium hydroxide (mCe(OH)3) was coated on the surface of sCeO2 modified by PEI: citric acid, hexadecyltrimethylammonium bromide, sodium salicylate, hexamethylenetetramine, and cerium chloride hexahydrate were added to solution D, and then cyclohexane was added to obtain solution E. Solution E was vigorously stirred for 1 hour, placed in an oil bath at 70°C for 7 hours, cooled, centrifuged, and washed with deionized water and ethanol to obtain a solid product, which was further dried in a drying oven at 60°C overnight to obtain solid cerium oxide nanospheres (sCeO2-mCe(OH)3) with surface coated mesoporous cerium hydroxide nanomaterials.

[0108] Finally, cerium oxide composite abrasives were obtained by high-temperature calcination: sCeO2-mCe(OH)3 was calcined to 600°C in a tubular furnace at a heating rate of 2°C / min in a N2 atmosphere and kept at 600°C for 6 hours. After that, the temperature was further increased to 600°C in air at a rate of 3°C / min and calcined for 2 hours to remove residual carbon, thereby obtaining mesoporous cerium oxide-coated solid cerium oxide nanospheres (sCeO2-mCeO2), i.e., cerium oxide composite abrasives.

[0109] In this embodiment, the molecular weight of polyethyleneimine is 10000 Da, the concentration of sCeO2 in solution C is 0.15 g / L, the concentration of polyethyleneimine is 0.25 g / L, and the mass ratio of polyethyleneimine to solid cerium oxide nanospheres is 5:3.

[0110] The mass ratio of sodium salicylate to solid cerium oxide nanospheres is 5:1, the mass ratio of citric acid, hexadecyltrimethylammonium bromide, sodium salicylate, hexamethylenetetramine, and cerium chloride hexahydrate is 1:20:15:3:15, and in solution E, the concentration of citric acid is 0.1 g / L, the concentration of hexadecyltrimethylammonium bromide is 2 g / L, the concentration of sodium salicylate is 1.5 g / L, the concentration of hexamethylenetetramine is 0.3 g / L, the concentration of cerium chloride hexahydrate is 1.5 g / L, and the volume ratio of cyclohexane to deionized water is 3:10.

[0111] Figure 2 a- Figure 2 b is a transmission electron microscope (TEM) image of the cerium oxide composite abrasive sCeO2-mCeO2 prepared in this example. Figure 2 It can be seen that it has an obvious core-shell structure, and the mesoporous cerium oxide material with lower density is evenly coated on the surface of the solid cerium oxide nanospheres with higher density. The overall structure is a spherical structure with a diameter of about 170nm, in which the thickness of the mesoporous cerium oxide shell is about 20nm.

[0112] Comparative Example 1

[0113] The difference between this comparative example and Example 7 is that polyethyleneimine (PEI) is not used to perform surface modification treatment on sCeO2.

[0114] Figure 3 is a transmission electron microscope (TEM) image of the cerium oxide composite material prepared by the above treatment. Figure 3 It can be seen that only part of the solid cerium oxide nanospheres are coated with mesoporous cerium oxide materials, and the coating is relatively uneven. It can be seen that surface modification of sCeO2 by PEI is the key to coating the mesoporous cerium hydroxide nanomaterials on the surface of solid cerium oxide nanospheres, and it helps to obtain more uniformly surface-coated solid cerium oxide nanospheres (sCeO2-mCe(OH)3) with mesoporous cerium hydroxide nanomaterials.

[0115] Performance Test:

[0116] The sCeO2 prepared in Example 2 and the sCeO2-mCeO2 prepared in Example 7 were characterized by physical and chemical properties, including X-ray diffraction analysis (XRD), N2 adsorption-desorption isotherm analysis, pore size distribution analysis, and X-ray photoelectron spectroscopy analysis (XPS):

[0117] Figure 4 The XRD curves of sCeO2 and sCeO2-mCeO2 are shown in Figure 2. Figure 4It can be seen that the characteristic peak positions of the XRD curves of sCeO2 and sCeO2-mCeO2 are consistent with the standard card PDF#34-0394 of CeO2, and the characteristic diffraction peaks of sCeO2-mCeO2 are enhanced after mesoporous cerium oxide coating, indicating that sCeO2 and sCeO2-mCeO2 are both CeO2 with cubic fluorite structure.

[0118] Figure 5 is the N2 adsorption-desorption isotherm of sCeO2-mCeO2, Figure 6 is the pore size distribution diagram of sCeO2-mCeO2, through Figure 5 as well as Figure 6 It can be seen that sCeO2-mCeO2 exhibits a type IV isotherm with a H3 hysteresis loop, which is a characteristic of porous materials, and its specific surface area is 58.119 m 2 / g, pore volume is 0.134cm 3 / g, pore diameter is 12.303nm.

[0119] Figure 7 is the XPS curve of sCeO2 and sCeO2-mCeO2. It can be seen from Figure 7 that compared with sCeO2, the content of trivalent cerium ions in sCeO2-mCeO2 formed after mesoporous cerium oxide coating is increased from 18.36% to 19.2%, indicating that the mesoporous structure of the coating shell has a rich pore structure and a large specific surface area, as well as a higher trivalent cerium ion content and better chemical reaction activity.

[0120] Application examples:

[0121] The sCeO2-mCeO2 composite abrasive prepared in Example 7 was prepared into a polishing liquid with a mass fraction of 0.2% using water as solvent, and the pH value of the polishing liquid was adjusted to 4 with acetic acid. After ultrasonic dispersion for 20 minutes, it was used for polishing silicon oxide wafers.

[0122] Generally speaking, a solution with a Zeta potential greater than 30 mV is considered to have good stability. The above polishing solution was taken and its Zeta potential was measured to be 40.07 mV. It can be seen that the polishing solution prepared with sCeO2-mCeO2 composite abrasive has relatively good stability.

[0123] Take the polishing liquid prepared above, and polish the silicon oxide wafer under the process conditions of polishing pressure of 2.84psi, polishing disk speed of 57r / min, polishing head speed of 63r / min, polishing liquid flow rate of 400mL / min, and polishing time of 1min. Record the mass loss of the wafer after polishing, and calculate the removal rate of the wafer material.

[0124] Figure 8 is an AFM morphology of the surface of the silicon oxide wafer after polishing. It has been measured that the roughness Ra value is 0.155nm and the Rq value is 0.195nm within the range of 5μm×5μm on the crystal surface. The material removal rate MRR is calculated to be 127nm / min. It can be seen that the polishing liquid prepared with sCeO2-mCeO2 composite abrasives can achieve a higher polishing rate while achieving a lower roughness polishing effect. In addition, after testing, when the mass concentration of the above-mentioned polishing liquid is 0.5%, the material removal rate MRR is doubled.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cerium oxide composite abrasive grain having a core-shell structure, characterized in that: It includes a core composed of solid cerium oxide nanospheres and a coating shell composed of mesoporous cerium oxide nanomaterials.

2. The cerium oxide composite abrasive grain having a core-shell structure according to claim 1, characterized in that: The inner core is prepared by surface modification of solid cerium oxide nanospheres using polyethyleneimine.

3. The cerium oxide composite abrasive grain having a core-shell structure according to claim 1, characterized in that: The diameter of the core is 100-200 nm, and the thickness of the coating shell is 10-50 nm.

4. The cerium oxide composite abrasive grain having a core-shell structure according to claim 3, characterized in that: The diameter of the core is 100-160 nm, and the thickness of the coating shell is 10-25 nm.

5. A method for preparing the cerium oxide composite abrasive grains having a core-shell structure according to any one of claims 1 to 4, characterized in that: The steps include: S1: Preparation of solid cerium oxide nanospheres by hydrothermal method; S2: Surface modification of solid cerium oxide nanospheres by polyethyleneimine; S3: The mesoporous cerium oxide nanomaterial is coated on the surface of the solid cerium oxide nanospheres after surface modification by an in-situ chemical precipitation method to obtain cerium oxide composite abrasives.

6. The method for preparing the cerium oxide composite abrasive grains having a core-shell structure according to claim 5, characterized in that: Step S1 includes the following steps: S11: subjecting a cerium source, a structure directing agent, and a precipitating agent to a hydrothermal reaction to obtain a cerium oxide precursor; S12: calcining the cerium oxide precursor to obtain solid cerium oxide nanospheres; In step S11, the cerium source is cerium nitrate hexahydrate, the structure directing agent is polyethylene glycol, and the precipitant is urea; the molar ratio of urea to cerium nitrate hexahydrate is 25-150, and the molecular weight of polyethylene glycol is 4000-20000Da; the temperature of the hydrothermal reaction is 90-110°C, and the time of the hydrothermal reaction is 2.5-3.5h; In step S12, calcination is performed in an air atmosphere at a temperature of 500-600° C. and a calcination time of 2-4 hours.

7. The method for preparing the cerium oxide composite abrasive grains having a core-shell structure according to claim 5, characterized in that: Step S2 includes the following steps: The solid cerium oxide nanospheres are dispersed in water, polyethyleneimine is added, ultrasonically reacted for 20-30 minutes, and then post-treated to obtain solid cerium oxide nanospheres with surface modification. The molecular weight of polyethyleneimine is 10000-15000 Da.

8. The method for preparing the cerium oxide composite abrasive grains having a core-shell structure according to claim 5, characterized in that: Step S3 includes the following steps: S31: adding the surface-modified solid cerium oxide nanospheres, citric acid, hexadecyltrimethylammonium bromide, sodium salicylate, hexamethylenetetramine, cerium chloride hexahydrate and cyclohexane into deionized water, stirring the mixture, and then reacting the mixture under heating and stirring conditions to obtain solid cerium oxide nanospheres with mesoporous cerium hydroxide nanomaterials coated on the surface; S32: calcining the solid cerium oxide nanospheres whose surfaces are coated with mesoporous cerium hydroxide nanomaterials to obtain cerium oxide composite abrasive particles.

9. The method for preparing the cerium oxide composite abrasive grains having a core-shell structure according to claim 8, characterized in that: In step S31, the mass ratio of sodium salicylate to solid cerium oxide nanospheres is 4:1-6:

1. After each component is added to deionized water, the concentration of citric acid is 0.05-0.15 g / L, the concentration of hexadecyltrimethylammonium bromide is 1-3 g / L, the concentration of sodium salicylate is 1-2 g / L, the concentration of hexamethylenetetramine is 0.2-0.4 g / L, the concentration of cerium chloride hexahydrate is 1.5-2 g / L, and the volume ratio of cyclohexane to deionized water is (2-4):(9-11); the stirring time is 1-2 h, the heating temperature is 60-80 ° C, and the reaction time is 7-8 h; In step S32, the solid cerium oxide nanospheres with the surface coated with the mesoporous cerium hydroxide nanomaterial are first subjected to a first-stage calcination treatment under a protective atmosphere, and then the solid cerium oxide nanospheres with the surface coated with the mesoporous cerium hydroxide nanomaterial are subjected to a second-stage calcination treatment under an air atmosphere; The calcination temperature of the first stage calcination treatment is 500-600℃, and the calcination time is 4-6h; The calcination temperature of the second stage calcination treatment is 500-600°C and the calcination time is 2-4h.

10. Use of the cerium oxide composite abrasive grains according to any one of claims 1 to 4 or the cerium oxide composite abrasive grains prepared by the preparation method according to any one of claims 5 to 9, characterized in that: The cerium oxide composite abrasive grains are used in polishing liquid.

Citation Information

Patent Citations

  • Core-shell cladding structure composite particle, preparation method and uses thereof

    CN106987229A

  • Cerium dioxide micro-sphere with multistage core-shell structure, preparation method of cerium dioxide micro-sphere and application of cerium dioxide micro-sphere

    CN108408756A

  • Liquid dispersions and powders of cerium-based core-shell particles, methods for their production and their use in polishing

    CN114599754A

  • CMP abrasive, polishing method, and production method for semiconductor device

    JP2004277474A

  • Abrasive and manufacturing method thereof

    JP2012011526A